2022
DOI: 10.1080/16506073.2022.2053571
|View full text |Cite
|
Sign up to set email alerts
|

A SMART approach to personalized care: preliminary data on how to select and sequence skills in transdiagnostic CBT

Abstract: Given that over 20 million adults each year do not receive care for their mental health difficulties, it is imperative to improve system-level capacity issues by increasing treatment efficiency. The present study aimed to collect feasibility/acceptability data on two strategies for increasing the efficiency of cognitive behavioral therapy: (1) personalized skill sequences and (2) personalized skill selections. Participants (N = 70) with anxiety and depressive disorders were enrolled in a pilot sequential multi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Potential participants were eligible for the study if they met criteria for at least one of the following disorders 1 : generalized anxiety disorder (GAD; n = 33; 47.1%), major depressive disorder (MDD; n = 19; 27.1%), social anxiety disorder (SAD; n = 16; 22.9%), persistent depressive disorder (PDD; n = 12; 17.1%), obsessive‐compulsive disorder (OCD; n = 5; 7.1%), panic disorder (PD; n = 4; 5.7%), posttraumatic stress disorder (PTSD; n = 3; 4.3%), acute stress disorder (ASD; n = 1; 1.4%), or agoraphobia (AG; n = 1; 1.4%). Complete diagnostic information is available in Sauer‐Zavala et al ( 2022 ). Potential participants were excluded for exhibiting symptoms requiring more intensive treatment (i.e., mania in the past year; acute suicidality; substance use disorder in the past 3 months; psychotic features); receiving ≥5 sessions of CBT in the past 5 years; being unwilling to stop concurrent treatment for an emotional disorder; or being unwilling to maintain a stable dosage of medication during participation.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Potential participants were eligible for the study if they met criteria for at least one of the following disorders 1 : generalized anxiety disorder (GAD; n = 33; 47.1%), major depressive disorder (MDD; n = 19; 27.1%), social anxiety disorder (SAD; n = 16; 22.9%), persistent depressive disorder (PDD; n = 12; 17.1%), obsessive‐compulsive disorder (OCD; n = 5; 7.1%), panic disorder (PD; n = 4; 5.7%), posttraumatic stress disorder (PTSD; n = 3; 4.3%), acute stress disorder (ASD; n = 1; 1.4%), or agoraphobia (AG; n = 1; 1.4%). Complete diagnostic information is available in Sauer‐Zavala et al ( 2022 ). Potential participants were excluded for exhibiting symptoms requiring more intensive treatment (i.e., mania in the past year; acute suicidality; substance use disorder in the past 3 months; psychotic features); receiving ≥5 sessions of CBT in the past 5 years; being unwilling to stop concurrent treatment for an emotional disorder; or being unwilling to maintain a stable dosage of medication during participation.…”
Section: Methodsmentioning
confidence: 99%
“…The treatment consisted of the five core modules of the UP, with all but one (i.e., Countering Emotional Behaviors) delivered over two weekly, 50–60‐min individual sessions in a randomized order (see Study Design below). Four therapists (a licensed clinical psychologist, a post‐doctoral fellow, and two advanced clinical psychology graduate students; two men, two women) provided the treatment and demonstrated good adherence (Sauer‐Zavala et al, 2022 ). In previous research (Sakiris & Berle, 2019 ) and the current sample (Sauer‐Zavala et al, 2022 ), the UP demonstrated efficacy in reducing anxiety and depression.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations